2016
DOI: 10.1371/journal.pone.0162654
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of SCCmec Elements in Staphylococcus aureus as Observed in South-Eastern Germany

Abstract: SCCmec elements are very important mobile genetic elements in Staphylococci that carry beta-lactam resistance genes mecA/mecC, recombinase genes and a variety of accessory genes. Twelve main types and a couple of variants have yet been described. In addition, there are also other SCC elements harbouring other markers. In order to subtype strains of methicillin-resistant S. aureus (MRSA) based on variations within their SCCmec elements, 86 markers were selected from published SCC sequences for an assay based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 36 publications
3
95
1
Order By: Relevance
“…CC22 MRSA are extremely common in Western Europe, but the rook isolates were not identical to the ubiquitous Barnim/UK-EMRSA-15 epidemic strain differing in SCC mec subtype (IVc rather than IVh; [77]) and presence of PVL genes. They were identical to a strain observed in several Middle Eastern countries and people with Middle Eastern travel history [109,127,128,129,130]. …”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…CC22 MRSA are extremely common in Western Europe, but the rook isolates were not identical to the ubiquitous Barnim/UK-EMRSA-15 epidemic strain differing in SCC mec subtype (IVc rather than IVh; [77]) and presence of PVL genes. They were identical to a strain observed in several Middle Eastern countries and people with Middle Eastern travel history [109,127,128,129,130]. …”
Section: Resultssupporting
confidence: 72%
“…They did not carry relevant resistance or toxin genes. The two Austrian isolates carried an isolated recombinase homologue ccrAA and reacted with new experimental probes ( opp3B ; ACSQ01000050.1 [4287:4313] and opp3C -C427 ACSQ01000050.1 [5150:5174]; [129]) indicating the presence of a type 3 ACME element.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The J regions are cassette components that may contain determinants for additional antimicrobial resistance; thus, within the SCCmec we can also find resistance genes to other non-β-lactam antibiotics such as erythromycin, clindamycin, tetracycline, aminoglycosides, clindamycin, among others [81]. Furthermore, there are also determinants of virulence and resistance to heavy metals within the SCCmec [82]. Currently, there are many strains that carry non-typed SCCmec elements or even with two types of ccr and or mec complex, and so there is still much to discover about the SCCmec system.…”
Section: Sccmec Typingmentioning
confidence: 99%
“…In addition, strain NK_18 (CC20, ST389, t2094) was classified as resistant to oxacillin, although neither mecA/ mecC nor other staphylococcal cassette chromosomeassociated genes were detected by DNA microarray. It has recently been shown that the commonly known 12 SCCmec types and their variants are only a fraction of the true diversity of SCCmec elements (Monecke et al, 2016(Monecke et al, , 2018. Therefore, a modification of the respective genomic elements or a variant not covered by the microarray used may be present in NK_18.…”
Section: Discussionmentioning
confidence: 99%